A SiO2 layer on PEO-treated Mg for enhanced corrosion resistance and bone regeneration - Qiu, Longhai; Zhang, Chi; Yang, Xiaoming; Peng, Feng; Huang, Yuliang; He, Yue (Frontiers in Bioengineering and Biotechnology, 2022)
Magnesium (Mg) is most potential biodegradable metal for orthopedic applications and plasma electrolytic oxidation (PEO) is widely studied as the corrosion protection coating on Mg-based implants. However, the porous structure and easily formed cracks in fluid is disadvantage for its long-term corrosion protection. Herein, we fabricated a SiO2 layer on PEO coated Mg to inhibit the crack formed on PEO layer as well as prevent the permeation of corrosive fluid. The thin SiO2 didn’t alter the surface morphology of the PEO layer, but hugely enhanced the corrosion resistance. In vitro cell culture of rBMSCs demonstrated the good cytocompatibility and osteogenic induction ability of SiO2 modified PEO coating which can be ascribed to Mg and Si ions released from the coating. Furthermore, with continuous released Mg and Si ions, the as-prepared implant showed superior osteogenesis and osteointegrtaion in rat bone implantation model. In summary, this newly designed Mg-based implants show promising prospects for orthopedic applications.